ANALISIS KALOR PADA MINICHANNEL PENDINGIN BATERAI PESAWAT ELEKTRIK DENGAN METODE CFD - Muhammad Bayu Adi Kusuma; Gaguk Marausna; Farid Jayadi (Sekolah Tinggi Teknologi Kedirgantaraan, 2022)
The aviation industry has changed the mass and private transportation industry, this type of air transportation has a very high negative impact on the atmosphere because of its very high fuel consumption and emitting a lot of pollutants so that future aircraft will lead to 2 types of aircraft, namely Hybrid-Electric Aircraft and All-Electric Aircraft. But the weakness in the battery is heavy and must have a long life time. The battery uses a minichannel and fluid as a heat transfer medium. The battery used in most aircraft is Lion. Then the desired result is how the speed is suitable for the minichannel as cooling the inner battery, because speed greatly affects convection. This research method uses a simulation to determine the flow conditions in the minichannel and the variation used is the Reynold number ranging from 500 to turbulent 5500, the result of the simulation is that if the Reynold number is larger and the flow velocity is greater, the outlet temperature value will be smaller, the inlet temperature by testing 20 °C., the results obtained are the higher the Reynold number, the higher the speed, and the lower the outlet temperature. The flow in the minichannel changes as the Reynolds number increases.